The price - Yoder, Pablo (Harrisonburg, VA : Vision Publishers, 2012)
Over a period of 5 years, while serving as Mennonite missionaries in Nicaragua, Pablo Yoder and his wife were robbed repeatedly. Intrigued by what he'd learned about the robbers, Yoder investigated further and put what he learned into this book, telling the story from the robbers' point of view.
A life gone awry -- Skinned alive -- A blasphemer's pay -- The price paid in full.
"A sequel of the Waslala robber stories" -- Cover.
Description based on print version record.
Keywords: Mennonites -- Nicaragua; Missions -- Nicaragua; Robbery -- Nicaragua; RELIGION / Christian Ministry / Missions; Electronic books